Integrasi Sains-Islam: Telaah Kritis Epistemologi Ziauddin Sardar dan Relevansinya bagi Perguruan Tinggi Keagamaan Islam Negeri Indonesia - Fian, Khafifatul; Mawardi, Kholid (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
Differences in views cause the need for scientific integration to create harmony. This is one of the efforts that need to be discussed and realized to minimize a dichotomy of science. This paper aims to analyze the integration of Islamic-science through a critical review of Ziauddin Sardar and its relevance in PTKIN. This paper includes the type of literature research with the acquisition of data collected through primary sources derived from Ziauddin Sardar's: